Metal–organic framework sensors for sustainable agriculture and environmental monitoring: Engineering, mechanisms, and future perspectives - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Muhammad Ali Amir; Waqas Haider; Hien Huu Nguyen; Athakorn Promwee (Environmental Nanotechnology, Monitoring & Management, 2026)

Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Exogenous dopamine alleviates chilling injury of sapodilla (Manilkara zapota) fruit by modulating reactive oxygen species and ascorbate-glutathione cycle activities - Sajid Ali; Syed Muhammad Kashan Haider; Safina Naz; Hafiz Umer Javed; Aamir Nawaz; Shaghef Ejaz; Muhammad Shahzad Saleem (Postharvest Biology and Technology, 2026)

Slope gradients mediate the effects of newly returned crop residues on soil nutrient dynamics and microbial diversity in Mollisol maize monoculture systems in Northeast China - Anwar Zeb; Liang-Jun Hu; Xu Li; Gohar Ali; Atteqa Akbar; Sarfraz Ahmed; Muhammad Awais Haider; Amrozia Naz (Agriculture, Ecosystems & Environment, 2026)

Phytochemical-rich extract of Psidium guajava ameliorates letrozole-induced PCOS in female rats by modulating the NF-κB inflammatory pathway - Hao Xu; Palwasha Haider; Majid Manzoor; Rida Siddique; Hina Manzoor; Muhammad Yasir Ali; Rizwan Rashid Bazmi; Liaqat Hussain; Ping Wang (Tissue and Cell, 2026)

A 25-year analysis of intracerebral hemorrhage mortality trends among patients with essential hypertension: Insights from the CDC WONDER database (1999–2024) - Mohammad Hamza Bin Abdul Malik; Muhammad Arham; Muhammad Awais Bin Abdul Malik; Allah dad; Anfal Hamza; Ayesha Ihsan; Tahira Nazir; Faseeh Haider; Ali Haq; Muhammad Salman Sabri (Next Research, 2026)

Recent advances in nZVI@MOF composites for Cr(VI) removal: A comprehensive review - Safina Zafar; Shumaila Bibi; Mohamed H. Helal; Haider Ali; Guilherme Luiz Dotto; Zeinhom M. El-Bahy; Muhammad Ahmad Wattoo; Aziz ur Rehman (Journal of Environmental Chemical Engineering, 2026)

Bioadaptive metal–organic frameworks in sustainable agriculture: Integrated crop protection, nutrient delivery, and beneficial microbial protection - Irfan Haidri; Muhammad Qasim; Qudrat Ullah; Ebadet Ali; Muhammad Ali Amir; Waqas Haider; Athakorn Promwee (Physiological and Molecular Plant Pathology, 2026)

Correction to: Climate‐driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Integrative mechanisms of photoperiod and temperature regulation in insect diapause - Dilawar Abbas; Kamran Haider; Farman Ullah; Muhammad Yasir Ali; Umer Liaqat; Maolin Hou (Journal of Pest Science, 2026)

Redox-modulating metallic nanoparticles: mechanistic insights into pharmacological activity and cellular therapeutics - Muhammad Irfan; Umar Zeeshan; Haider; Ali Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

The role of Campylobacter group II phages in mitigating Campylobacter contamination across the poultry food chain: Current applications and future prospects - Muhammad Shahzad Rafiq; Syed Sami Haider; Ziyi Li; Muhammad Sarmad; Dongxin Ma; Muhammad Ali Khan; Junhao Wang; Shuaifeng Gu; Pan Tao; Muhammad Tanweer Khan; Haihong Hao (Food Research International, 2026)

Redox-responsive goethite-modified biochar regulates cadmium and arsenic translocation in rice via irrigation-driven iron plaque dynamics - Iftikhar Ali Ahmad; Sharjeel Haider; Muhammad Mehran; Zaryab Murad; Adnan Mustafa; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Research, 2026)

Edaravone dexborneol in acute ischemic stroke: a systematic review and meta-analysis of randomized trials with clinical and thrombectomy-specific subgroup analyses - Eman Tariq; Hooriya Ahmed; Tayyaba Ikram Qazi; Abdul Muhaimin; Aleena Amir Malik; Javeria Soomro; Rahimeen Qureshi; Zainab Murtaza; Sarum Ali Khan; Wajeeha Komal; Hadia Tanveer; Rida Ameer; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Erratum to: CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Evaluation of the antiulcer activity of methanolic extract of Bidens biternata on experimental rats via involvement of the PGE2/Nrf2/HO-1/NF-κB/Caspase-3 pathways - Muhammad Murtaza; Mohammad Khalid; Gaurav Gupta; Haider Ali; Kavita Goyal; Adil Abalkhail; Fahad M. Aldakheel; Farhan R. Khan; Ameeduzzafar Zafar (South African Journal of Botany, 2026)

Deciphering the synergy of eudragit and polyethylene glycol supported cobalt oxide for catalytic, electrocatalytic and antibacterial activity: Computational insights - Atika; Muhammad Imran; Iram Shahzadi; Ali Haider; Sumaira Rasool; Anwar Ul-Hamid; Norah A. Albassami; Muhammad Ikram (Journal of Water Process Engineering, 2026)

Evolution and Biogeography of the Genus Heteropoda (Heteropodinae: Sparassidae) Across Southeast Asia - Shakal Khan Korai; Amir Khan Korai; Shengnan Li; Kamil Kabir; Kamran Haider; Muhammad Raheel Tariq; Arif Ali; Xiaoshan Wang (Zoologica Scripta, 2026)
Heteropoda huntsman spiders are large, fast‐moving predators widely distributed across tropical and subtropical regions, where they function as important nocturnal hunters. Despite their ecological prominence, the evolutionary and biogeographic history of the genus remains poorly resolved. Here, we analysed a six‐locus dataset (two mitochondrial and four nuclear genes) to estimate divergence times and reconstruct ancestral ranges within Heteropoda using Bayesian phylogenetic and statistical biogeographic approaches, and we assessed broad climatic suitability using genus‐level ecological niche modelling. Time‐calibrated analyses support the monophyly of Heteropoda and indicate that crown diversification began during the early Oligocene (~30 Ma; 95% HPD: 18–41 Ma). A primary split between Australasian and Asian lineages is inferred near the Oligocene–Miocene transition (~23 Ma; 95% HPD: 14–33 Ma), followed by radiation within Southeast and East Asia. Ancestral‐area reconstructions consistently recover Australasia as a key ancestral component and suggest repeated dispersal and isolation across the Sunda–Wallacea interface under conditions of long‐term tectonic instability. Ecological niche modelling identifies temperature, precipitation, and elevation as major correlates of climatic suitability, consistent with the predominance of Heteropoda in warm and humid environments. Together, these results provide an integrated temporal, spatial, and ecological framework for understanding diversification and present‐day distribution of Heteropoda across Southeast Asia and adjacent regions.

Influence of weather patterns on ground-level ozone pollution: a 2023 summer case study in Jilin City with health risk assessment - Anees Akhtar; Chunsheng Fang; Ju Wang; Sarfraz Ahmed; Muhammad Awais Haider; Haider Ali; Muhammad Naveed; Samama Tariq (Environmental Monitoring and Assessment, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

CRISPR, Omics, and Nanotechnology: A Triangular Strategy for Next-Generation Wheat Improvement - Muhammad Mubashar Zafar; Ayaz Haider Khan; Ali Murtaza; Muhammad Asim Jamil; Hafsa; Muhammad Munem Khan; Muhammad Awais; Hina Firdous (Journal of Crop Health, 2026)

Green-Synthesized Gold Nanoparticles from Fortunella Margarita (Kumquat) Leaf Extract for Broad-Spectrum Antifungal Control of Postharvest Fruit Crop Pathogens - Bismillah Mubeen; Ammarah Hasnain; Haider Ali; Muhammad Nadeem Khan; Maymoona Saher; Muhammad Umer Iqbal; Syed Atif Hasan Naqvi (Applied Fruit Science, 2026)

Rock–water interactions in the coal mining area of Dukki, Balochistan, determine the drinking and irrigation suitability of groundwater: an in-depth risk assessment - Ghazala Mohammad Ali; Muhammad Akhtar; Muhammad Faraz Bhatti; Fazal Adnan; Malik Badshah; Ghayas Haider Sajid; Ghulam Haider (Environmental Geochemistry and Health, 2026)

Sustainable valorization of olive pomace industrial side stream via explainable machine learning guided biochar pyrolysis - Muhammad Ali Haider; Jawad Gul; Muhammad Nouman Aslam Khan; Dagmar Juchelkova (Process Safety and Environmental Protection, 2026)

Selenium supplementation and male fertility: Mechanistic insights and therapeutic potential - Neeraj Patel; Riya Mishra; Muhammad Afzal; Surya Nath Pandey; Haider Ali; Nardev Singh; Rakhi Mishra; Mohd Imran (Journal of Trace Elements in Medicine and Biology, 2026)

Navigating green Seas: An open-source tool for costing the development of green shipping corridors - Peter Ellersdorfer; Muhammad Haider Ali Khan; Michaël Lejeune; Annika Kerwick; Tahlia Nolan; Jorge Garcia Martinez; Alannah Darling; Iain MacGill; Rahman Daiyan (Fuel, 2026)

Performance of ambient cured fly ash-slag based geopolymer concrete reinforced with glass wool and nylon fibres - Hussnain Haider; Shehroze Ali; Muhammad Talha Ghafoor (Innovative Infrastructure Solutions, 2026)

Climate-driven insect pest outbreaks and food security risks: a review of adaptive strategies for resilient agriculture - Kamran Haider; Dilawar Abbas; Farman Ullah; Muhammad Ijaz; Muhammad Ikram; Kamil Kabir; Khalid Ali Khan; Jose Galian (Journal of Pest Science, 2026)

Computationally guided synthesis and biological profiling of chalcones as antioxidant and anti-inflammatory activities - Hafiz Aamir Ali Kharl; Muhammad Naeem; Shakira Ghazanfar; Arifa Mehreen; Hasnain Haider; Sumel Ashique; Sabina Yasmin; Fatimah M. Al-Salem; Md Yousuf Ansari (Inflammopharmacology, 2026)

Combined use of proline and microbes on yield attributes, photosynthetic efficiency, water relations, nutrient acquisition and antioxidative defense mechanisms of fennel plants under drought conditions - Tabish Ali Virk; Muhammad Zulqurnain Haider; Qasim Ali (Biologia Futura, 2026)

Genomic surveillance of Influenza, SARS-CoV-2, and RSV in patients from Islamabad and Rawalpindi, Pakistan: a 2023-24 perspective - Zunera Jamal; Syed Adnan Haider; Fahad Humayun; Qasim Ali; Rabia Hakim; Muhammad Salman; Massab Umair (Archives of Virology, 2026)

Mechanisms and thermodynamics underlying pressure-enhanced methanogenesis in production of renewable natural gas with carbon sequestration in coal seams - Weiting Zhang; Zaixing Huang; Huan He; Michael Urynowicz; Hongguang Guo; Fang-Jing Liu; Asif Jamal; Muhammad Ishtiaq Ali; Rizwan Haider (Chemical Engineering Journal, 2026)

Effects of nitrogen source and C/N ratio on methane production by anaerobic co-digestion of water bloom cyanobacteria and lignite - Yajie Chang; Huan He; Yuxiang Zhong; Weiting Zhang; Zaixing Huang; Michael Urynowicz; Hongguang Guo; Fang-Jing Liu; Asif Jamal; Muhammad Ishtiaq Ali; Rizwan Haider (Bioresource Technology Reports, 2026)

Management of canola aphids (Hemiptera: Aphididae) using potassium silicate (K2SiO3) in integration with Chrysoperla carnea Stephens - Dilawar Abbas; Umer Liaqat; Habib Ali; Tehniyat Fatima; Ammara Riaz; Inzamam Ul Haq; Zahid Mahmood Sarwar; Muhammad Abaid Ullah; Muhammad Adeel Ghafar; Kamran Haider; Muhammad Lubaid Khalid; Modhi O. Alotaibi; et al. (Journal of Plant Diseases and Protection, 2026)

Antibacterial Activity of Anthraquinones Isolated from Reynoutria Japonica Against Staphylococcus aureus: An in Silico and In Vitro Approach - Iqra Anam Khawaja; Sajid Ali; Muhammad Faheem; Syed Babar Jamal; Adnan Haider; Falak Niaz; Mi-Jeong Ahn; Mutiullah Khattak; Atif Ali Khan Khalil (Journal of Pharmaceutical Innovation, 2026)

Phytochemical Profiling and Evaluation of the Anti-inflammatory and Antinociceptive Effects of Lilium polyphyllum Bulb Using In Silico, In Vitro and In Vivo Models - Haider Ali; Shafiq Ur Rahman; Umair Sayad; Atif Ali Khan Khalil; Muzaffar Abbas; Muhammad Shahid (Journal of Pharmaceutical Innovation, 2026)

Gypsum-integrated, goethite-modified biochar enhances Cd and As immobilization in contaminated paddy soil under contrasting redox conditions - Iftikhar Ali Ahmad; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Hongqing Hu (Environmental Geochemistry and Health, 2026)

Retraction notice to “Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community” [Sci. Total Environ. 929 (2024) 172632] - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2026)

Explainable deep learning combined attention-based LSTM for building energy prediction: a framework from the perspective of supply side - Muhammad Saad Ul Haq; Wenjie Ji; Xingyu Pei; Shuli Liu; Yang Geng; Borong Lin; Haider Ali (Energy and Buildings, 2026)

Wheat-Berseem intercropping system enhances soil fertility, carbon sequestration and crop productivity under nutrient-deficient conditions - Zafar Iqbal; Sundas Bilal; Sana ur Rehman; Imran Haider; Maryam Saeed; Maqshoof Ahmad; Muhammad Ali Raza; Mehraj A. Abbasov; Walid Soufan (Plant and Soil, 2026)

Targeting gasdermin D–mediated pyroptosis: a precision anti-inflammatory strategy for acute and chronic lung diseases - Vijaya Paul Samuel; Muhammad Afzal; M. Arockia Babu; H. Malathi; Laxmidhar Maharana; Surya Nath Pandey; Haider Ali; Waleed Hassan Almalki; Salem Salman Almujri; K. Benod Kumar (Inflammopharmacology, 2026)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “coupled NOx production and electrochemical conversion processes for sustainable ammonium synthesis from air” [Chem. Eng. J. Volume 524 (2025) 168996] - Zhipeng Ma; Josh Leverett; Jodie A. Yuwono; Jian Pan; Shujie Zhou; Ding Zhang; Ming Zhang; Bingqiao Xie; Lingyi Peng; Muhammad Haider Ali Khan; Sergio L. Londono; Priyank V. Kumar; et al. (Chemical Engineering Journal, 2025)

Phenotypic Plasticity of Safflower Genotypes in Response to Contrasting Climatic Conditions - Obaid Afzal; Mukhtar Ahmed; Sahir Hameed Khattak; Muhammad Aqeel Aslam; Saida Komal; Maryam Murtaza; Farrukh Bashir; Aqeel Ahmad; Aliya Mirbaz; Haroon Ur Rasheed; Ghulam Muhammad Ali; Muhammad Usman; et al. (Plant Molecular Biology Reporter, 2025)

Coupled NOx production and electrochemical conversion processes for sustainable ammonium synthesis from air - Zhipeng Ma; Josh Leverett; Jodie A. Yuwono; Jian Pan; Shujie Zhou; Ding Zhang; Ming Zhang; Bingqiao Xie; Lingyi Peng; Muhammad Haider Ali Khan; Sergio L. Londono; Priyank V. Kumar; et al. (Chemical Engineering Journal, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

Targeting the senescence-associated secretory phenotype to modify osteoarthritis in aging - Muhammad Afzal; M. M. Rekha; Samir Sahoo; Surya Nath Pandey; Chandana Maji; Kavita Goyal; Haider Ali; Sachin Kumar Singh; Gaurav Gupta; Md Sadique Hussain (Inflammopharmacology, 2025)

Co-utilization of green manure with straw return enhances the stability of soil organic carbon by regulating iron-mediated stabilization of aggregate-associated organic carbon in paddy soil - Muhammad Mehran; Li Huang; Mingjian Geng; Yafen Gan; Jinyun Cheng; Qiang Zhu; Iftikhar Ali Ahmad; Sharjeel Haider; Adnan Mustafa (Soil and Tillage Research, 2025)

Precipitation of rare earth phosphates through apatite leach as by-product of nitrophos acid from unconventional phosphate deposit of carbonatite, Malakand, Pakistan - Farva Arshad; Munirah Atique Khan; Attiqa Nasir; Muhammad Haider Ali; Lubna Basit; Muhammad Nasir Siddique; Muhammad Nadeem (Hydrometallurgy, 2025)

Effects of calcite on biogenic methane production and microbial community structure in coal - Bei Zhang; Huan He; Qian Zhang; Xiuxiang Tao; Fengjuan Lan; Han Zhao; Linyong Chen; Hengxing Ren; Yanfei Zhang; Hongguang Guo; Fang-Jing Liu; Asif Jamal; et al. (Fuel, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Nano-engineered biochar enhances soil microbial interactions and maize transcriptomic pathways for cadmium detoxification - Muhammad Umair Yasin; Sajid Muhammad; Nana Chen; Fakhir Hannan; Muhammad Afzal; Zulqarnain Haider; Bahar Ali; Irshan Ahmad; Muhammad Rehman; Yinbo Gan (Journal of Hazardous Materials, 2025)

MnFe2O4 thin film electrodes via AACVD: A facile route for enhanced oxygen evolution reaction - Alishbah Zaka; Misha Aftab; Nudrat Fatima; Khola Mashood; Muhammad Adeel Asghar; Arshid Numan; Muhammad Sheraz Ahmad; Ali Haider; Mudassir Iqbal; Waqas Ali Shah; Muhammad Adil Mansoor (Fuel, 2025)

Phycocyanin as a sustainable future resource: A review on recent advancements, fundamental challenges, opportunities and applications - Haider Ali; Rashid Iftikhar; Muhammad Ali Inam; Muhammad Umer Abbas; Sahar Saleem; Faras Ahmad Shahbaz; Humayun Nadeem; Aleena Tahir; M. Momin (Bioresource Technology Reports, 2025)

Phosphorus Modified Biochar and Vermicompost Integration Alleviated Cd Phytotoxicity in Wheat (Triticum aestivum L.) by Improving Growth, Antioxidant Activities and Reducing Cd Uptake in Plants - Ahmad Ali; Zaffar Malik; Ghulam Hassan Abbasi; Muhammad Waseem; Muhammad Rizwan; Muhammad Ali; Sobia Afzal; Syed Farhan Haider Bukhari; Usama Ali Tahir (Journal of Soil Science and Plant Nutrition, 2025)

Managing water deficit in wheat through mulches and irrigation techniques in semi-arid regions - Salman Ahmad; Muhammad Aown Sammar Raza; Muhammad Ali; Rashid Iqbal; Muhammad Usman Aslam; Monika Toleikiene; Abd El-Zaher M. A. Mustafa; Humaira Rizwana; Imran Haider; Muhammad Zain; Saltanat Aghayeva; Ozhan Simsek; et al. (Cereal Research Communications, 2025)

Enhanced electrochemical performance of MoP2-based supercapacitor electrodes through doping with transition, post-transition, and rare earth metals - Mudassar Maraj; Mir Rehman Shabbir; Faisal Ali; Muhammad Hamza Naseer; Ali Haider Bhalli; Sarmad Ali; Nian Li; Xiuhong Li; Zhenyang Wang (Fuel, 2025)

Gum Arabic Organic Coating Maintains Freshness and Modulates Oxidative Stress by Augmenting the Antioxidant Activities of Harvested Ber Fruit - Alisha Noor; Ahmad Sattar Khan; Raheel Anwar; Sajid Ali; Rana Naveed Ur Rehman; Saqib Ayyub; Muhammad Haider Ali (Applied Fruit Science, 2025)

Synergistic performance of silver/polyacrylic acid doped ZrO2 nanostructures for dye degradation and bactericidal behavior with molecular docking analysis - Muhammad Ikram; Alvina Rafiq Butt; Sidra Bano; Sadia Naz; Sawaira Moeen; Anwar Ul-Hamid; Ali Haider; Amel Ayari-Akkari (Environment, Development and Sustainability, 2025)

Breakthrough in plasmonic enhanced MOFs: Design, synthesis, and catalytic mechanisms for various photocatalytic applications - Waqar Ahmad Qureshi; Syed Najeeb-Uz-Zaman Haider; Muhammad Adnan Qaiser; Shahid Khan; Weikang Wang; Rai Nauman Ali; Amjad Ali; Ahmad Naveed; Mohamed Hussein Abdurahman; Muhammad Usman Khan; Muhammad Tayyab; Lele Wang; et al. (Environmental Research, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Green-engineered calcium-doped carbon nanospheres enhance salt tolerance and growth in maize by modulating gene expressions and antioxidant defense mechanisms - Muhammad Haseeb Javaid; Bahar Ali; Asifa Neelam; Syed Asad Hussain Bukhari; Raheel Munir; Zulqarnain Haider; Muhammad Rehman; Hafiza Arooj Razzaq; Abdul Majeed; Yinbo Gan (Journal of Environmental Chemical Engineering, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Longevity mechanisms in cardiac aging: exploring calcium dysregulation and senescence - Neetu Agrawal; Muhammad Afzal; Waleed Hassan Almalki; Suhas Ballal; Girish Chandra Sharma; T. Krithiga; Rajashree Panigrahi; Suman Saini; Haider Ali; Kavita Goyal; Mohit Rana; Abida Khan (Biogerontology, 2025)

Simultaneous adsorption of cadmium and arsenic by goethite-modified rice straw-derived biochar in water and soil: interactive ion effects and co-adsorption mechanism - Iftikhar Ali Ahmad; Hongqing Hu; Md. Shoffikul Islam; Qingling Fu; Jun Zhu; Fei Miao; Muhammad Mehran; Sharjeel Haider; Zaryab Murad; Ayaz Ali (Environmental Monitoring and Assessment, 2025)

Effects of Zn2+ and Co2+ on methane production of Shengli lignite pretreated with H2O2 - Mengmeng Li; Yi Ren; Zaixing Huang; Huan He; Yuxiang Zhong; Han Zhao; Hengxing Ren; Linyong Chen; Fengjuan Lan; Yanfei Zhang; Hongguang Guo; Fang-Jing Liu; et al. (Fuel, 2025)

Interactive effects of soil moisture and temperature on chromium-induced microbial and enzymatic stress - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Muhammad Akmal; Muhammad Abid Ali Khan; Muhammad Umer Iqbal; Niaz Ahmad; Mahmoud Moustafa; Mohammed O. Alshaharni; Uthman Algopishi (World Journal of Microbiology and Biotechnology, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

The role of VEGF in vascular dementia: impact of aging and cellular senescence - Neetu Agrawal; Muhammad Afzal; Nawaid Hussain Khan; Subbulakshmi Ganesan; Mukesh Kumari; S. Sunitha; Aniruddh Dash; Kavita Goyal; Brajgopal Kushwaha; A. Rekha; Mohit Rana; Haider Ali (Biogerontology, 2025)

Harnessing the FOXO-SIRT1 axis: insights into cellular stress, metabolism, and aging - Saurabh Gupta; Muhammad Afzal; Neetu Agrawal; Waleed Hassan Almalki; Mohit Rana; Saurabh Gangola; Suresh V. Chinni; Benod Kumar.K; Haider Ali; Sachin Kumar Singh; Saurabh Kumar Jha; Gaurav Gupta (Biogerontology, 2025)

The interplay of p16INK4a and non-coding RNAs: bridging cellular senescence, aging, and cancer - Ashok Kumar Balaraman; Muhammad Afzal; Ehssan Moglad; M. Arockia Babu; G. Padma Priya; Pooja Bansal; Sumit Rajotiya; Benod Kumar Kondapavuluri; Imran Kazmi; Sami I. Alzarea; Kavita Goyal; Haider Ali (Biogerontology, 2025)

The multifaceted roles of gut microbiota in insect physiology, metabolism, and environmental adaptation: implications for pest management strategies - Kamran Haider; Dilawar Abbas; Jose Galian; Muhammad Adeel Ghafar; Kamil Kabir; Muhammad Ijaz; Mehboob Hussain; Khalid Ali Khan; Hamed A. Ghramh; Abbas Raza (World Journal of Microbiology and Biotechnology, 2025)

Genomic selection, gene editing, and reproductive biotechnology: a triad for the improvement of native buffalo breeds in a developing country perspective like Pakistan - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ali Haider Saleem; Qudrat Ullah; Ghulam Abbas; Babar Maqbool; Masroor Ellahi Babar; Yanzhen Bi; Farhan Farooq (Tropical Animal Health and Production, 2025)

Impacts of Conservation Tillage on Agricultural Land Development: A Review - Xue Liang; Sana Ur Rehman; Wang Zhiqi; Muhammad Ali Raza; Imran Haider; Muhammad Hayder Bin Khalid; Amjad Saeed; Zafar Iqbal; Shroz Fatima; Ayesha Siddiqa; Muhammad Ansar; Shahzada Sohail Ijaz; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Corrigendum to ‘The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system’ [Environ. Pollut. 364P1 (2024) 125311] - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Targeting senescence and GATA4 in age-related cardiovascular disease: a comprehensive approach - Mohd Imran; Abdulmalik S. A. Altamimi; Muhammad Afzal; M. Arockia Babu; Kavita Goyal; Suhas Ballal; Pawan Sharma; Fadiyah Jadid Alanazi; Abeer Nuwayfi Alruwaili; Nouf Afit Aldhafeeri; Haider Ali (Biogerontology, 2025)

Chronic kidney disease and aging: dissecting the p53/p21 pathway as a therapeutic target - Kavita Goyal; Muhammad Afzal; Abdulmalik Saleh Alfawaz Altamimi; M. Arockia Babu; Suhas Ballal; Irwanjot Kaur; Sachin Kumar; M. Ravi Kumar; Ashish Singh Chauhan; Haider Ali; Moyad Shahwan; Gaurav Gupta (Biogerontology, 2025)

The Role of Gut Microbiota in Shaping Immune Responses in Tephritidae Fruit Fly and Prospective Implications for Management - Kamran Haider; Muhammad Sufian; Dilawar Abbas; Kamil Kabir; Muhammad Shamekh Ali; Yasmin Kausar; Muhammad Adeel Ghafar (Neotropical Entomology, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Titanium dioxide nanoparticles seed priming as a remedy for nickel-induced stress in maize through antioxidant enhancement and ultrastructural optimization - Muhammad Rehman; Abdul Salam; Bahar Ali; Irshan Ahmad; Muhammad Haseeb Javaid; Zulqarnain Haider; Raheel Munir; Muhammad Umair Yasin; Imran Ali; Chunyan Yang; Sajid Muhammad; Yinbo Gan (Journal of Environmental Management, 2025)

The protective roles of Oryza glumaepatula and phytohormone in enhancing rice tolerance to cadmium stress by regulating gene expression, morphological, physiological, and antioxidant defense system - Humera Ashraf; Fozia Ghouri; Shafaqat Ali; Syed Asad Hussain Bukhari; Fasih Ullah Haider; Minghui Zhong; Weiwei Xia; Xuelin Fu; Muhammad Qasim Shahid (Environmental Pollution, 2025)

Efficient removal of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS) from aqueous solution using modified biochar: Preparation, performance, and mechanistic insights - Waqas Niaz; Dahai Zhang; Zia Ahmad; Nan Shen; Waqas Haider; Imran Ali; Muhammad Usman; Abdul Majid; Sheikh Fahad Javaid; Muhammad Ahsan Amjed; Xianguo Li (Journal of Environmental Chemical Engineering, 2024)

Bioderived carbon quantum dots boost maize growth and photosynthesis by augmenting UV spectrum absorption and carbon assimilation regulatory genes - Zulqarnain Haider; Chunyan Yang; Irshan Ahmad; Samta Zia; Muhammad Haseeb Javaid; Muhammad Rehman; Muhammad Umair Yasin; Bahar Ali; Chen Nana; Yinbo Gan (Journal of Environmental Chemical Engineering, 2024)

A novel homozygous missense TTC12 variant identified in an infertile Pakistani man with severe oligoasthenoteratozoospermia and primary ciliary dyskinesia - Imtiaz Ali; Haider Ali; Ahsanullah Unar; Fazal Rahim; Khalid Khan; Sobia Dil; Tanveer Abbas; Ansar Hussain; Aurang Zeb; Muhammad Zubair; Huan Zhang; Hui Ma; et al. (Molecular Genetics and Genomics, 2024)

Improving salinity tolerance in wheat plants via inoculation with Azospirillum brasilense and Bacillus subtilis for enhanced biomass, growth and physiological process - Nazish Aijaz; Muhammad Saqlain Zaheer; Akhtar Hameed; Hafiz M. Usman Aslam; Muhammad Waqar Alam; Hasan Riaz; Jayanthi Barasarathi; Saltanat Aghayeva; Rani Bibi; Muhammad Waheed Riaz; Hafiz Haider Ali; Salim Manoharadas; et al. (Acta Physiologiae Plantarum, 2024)

Corrigendum: Drought-induced adaptive and ameliorative strategies in plants [Chemosphere 364 (2024) 143134] - Sharjeel Haider; Khadija Bibi; Venuste Munyaneza; Hao Zhang; Wen Zhang; Ayaz Ali; Iftikhar Ali Ahmad; Muhammad Mehran; Fangsen Xu; Chunlei Yang; Jinpeng Yang; Guangda Ding (Chemosphere, 2024)

From lake to fisheries: Interactive effect of climate and landuse changes hit on lake fish catch? - Shan-e-hyder Soomro; Muhammad Waseem Boota; Haider M. Zwain; Majid Rasta; Caihong Hu; Chengshuai Liu; Yinghai Li; Ao li; Jijun Chen; Chunyun Zhu; Sher Ali; Jiali Guo; et al. (Environmental Research, 2024)

Integrative multi-target analysis of Urtica dioica for gout arthritis treatment: a network pharmacology and clustering approach - Maryam Qasmi; Muhammad Mazhar Fareed; Haider Ali; Zarmina Khan; Sergey Shityakov (In Silico Pharmacology, 2024)

Drought-induced adaptive and ameliorative strategies in plants - Sharjeel Haider; Khadija Bibi; Venuste Munyaneza; Hao Zhang; Wen Zhang; Ayaz Ali; Iftikhar Ali Ahmad; Muhammad Mehran; Fangsen Xu; Chunlei Yang; Jinpeng Yang; Guangda Ding (Chemosphere, 2024)

One stone two birds: Endophytes alleviating trace elements accumulation and suppressing soilborne pathogen by stimulating plant growth, photosynthetic potential and defense related gene expression - Muhammad Imran; Zhongke Sun; Kamal A.M Abo-Elyousr; Haider Ali; Munirah F. Aldayel; Chengwei Li (Journal of Hazardous Materials, 2024)

Oryza glumaepatula and calcium oxide nanoparticles enhanced Cr stress tolerance by maintaining antioxidant defense, chlorophyll and gene expression levels in rice - Humera Ashraf; Fozia Ghouri; Minghui Zhong; Sardar Alam Cheema; Fasih Ullah Haider; Lixia Sun; Shafaqat Ali; Mohammed Ali Alshehri; Xuelin Fu; Muhammad Qasim Shahid (Journal of Environmental Management, 2024)

Managing antimony pollution: Insights into Soil–Plant system dynamics and remediation Strategies - Fasih Ullah Haider; Usman Zulfiqar; Noor ul Ain; Tariq Mehmood; Umed Ali; Luis Carlos Ramos Aguila; Yuelin Li; Kadambot H.M. Siddique; Muhammad Farooq (Chemosphere, 2024)

Development of energy efficient flower-shaped defective TiO2 materials for wastewater remediation of agro-industries and oil refineries - Rab Nawaz; Marlia Mohd Hanafiah; Sajjad Haider; Muzammil Anjum; Mujahid Ali; Rawaiz Khan; Sammia Khurshid; Shafi Ullah; Muhammad Aqif; Adnan Haider; Zaher Abdel Baki (Process Safety and Environmental Protection, 2024)

Smartphone-assimilated colorimetric sensor for sub-nanomolar emamectin detection via KA30 capped silver nanoparticles in food, bio-fluids and water samples - Aziz Balouch; Kashif Hussain; Ayman Nafady; Abdul Jabbar; Sufian Rasheed; Sumaira Kanwal; Sadia Haider; Razium Ali Soomro; Sirajuddin; Muhammad Raza Shah (Food Chemistry, 2024)

A novel computational methodology to design solar radiation absorbing glass - Faraan Fareed; Uzma Habib; Hafiz Ali Haider Sehole; Salma Sherbaz; Muhammad Bilal Khan Niazi; Adnan Maqsood (Energy and Buildings, 2024)

Silicon and Biochar Synergistically Stimulate Nutrients Uptake, Photosynthetic Pigments, Gaseous Exchange and Oxidative Defense to Improve Maize Growth Under Salinity - Sajid Mahmood; Samir G. Al-Solaimani; Samrah Shams; Sahar Naveed; Basit Haider; Muhammad Naveed; Rehmat Ali; Muhammad Waqas (Water, Air, & Soil Pollution, 2024)

RETRACTED: Almond shell-derived biochar decreased toxic metals bioavailability and uptake by tomato and enhanced the antioxidant system and microbial community - Muhammad Imran Ghani; Mohammad Abass Ahanger; Tanveer Ali Sial; Sajjad Haider; Junaid Ali Siddique; Ruidong Fan; Yanjiang Liu; Esmat F. Ali; Manish Kumar; Xing Yang; Jörg Rinklebe; Xiaoyulong Chen; et al. (Science of The Total Environment, 2024)

Qualitative and quantitative analysis of high-value metabolites from callus culture of Alcea rosea L. - Hasnat Tariq; Anisa Andleeb; Sannia Batool; Urooj Ali; Muhammad Waqas; Abdul Wahab; Gouhar Zaman; Samantha Drouet; Nathalie Giglioli-Guivarc’h; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

The impact of formaldehyde exposure on lung inflammatory disorders: Insights into asthma, bronchitis, and pulmonary fibrosis - Asif Ahmad Bhat; Muhammad Afzal; Ahsas Goyal; Gaurav Gupta; Riya Thapa; Waleed Hassan almalki; Imran Kazmi; Sami I. Alzarea; Moyad Shahwan; Keshav Raj Paudel; Haider Ali; Dipak Sahu; et al. (Chemico-Biological Interactions, 2024)

The synergistic potential of biochar and nanoparticles in phytoremediation and enhancing cadmium tolerance in plants - Muhammad Umair Yasin; Zulqarnain Haider; Raheel Munir; Usman Zulfiqar; Muhammad Rehman; Muhammad Haseeb Javaid; Irshan Ahmad; Chen Nana; Muhammad Sulaman Saeed; Bahar Ali; Yinbo Gan (Chemosphere, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Concentration and distribution patterns of rare earth elements (REEs) in stream sediments of Pakistan - Zhihua Wang; Jun Hong; Xin Lin; Huishan Zhang; Yasir Shaheen Khalil; Naghma Haider; Mehboob Ur Rashid; Muhammad Jawad Zeb; Asad Ali Narejo (Journal of Geochemical Exploration, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Vegetable Plant Canopy Inhibits Soil Urease Activity and Reduces NH3 Losses Under p-Phenylenediamine (PPD)-Coated Urea Application - Sarah Shakeel; Rashid Mahmood; Ammara Fatima; Faisal Nadeem; Sajid Ali; Muhammad Saleem Haider (Journal of Soil Science and Plant Nutrition, 2024)

Border fences reduce potential for transboundary migration of Marco Polo Sheep (Ovis ammon polii) in the Pamir Plateau - Yingying Zhuo; Muyang Wang; Zhongjun Liu; Wenxuan Xu; Abdulnazarov Abdulnazar; Ali Madad Rajabi; Askar Davletbakov; Jibran Haider; Muhammad Zafar Khan; Nabiev Loik; Sorosh Poya Faryabi; Stefan Michel; et al. (Science of The Total Environment, 2024)

Chimaphila umbellata; a biotechnological perspective on the coming-of-age prince’s pine - Urooj Ali; Muhammad Mustajab Khan; Naveera Khan; Rida tul Haya; Muhammad Usama Asghar; Bilal Haider Abbasi (Phytochemistry Reviews, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Modulation of metal transporters, oxidative stress and cell abnormalities by synergistic application of silicon and titanium oxide nanoparticles: A strategy for cadmium tolerance in rice - Mingyu Lai; Fozia Ghouri; Samreen Sarwar; Sarah Owdah Alomrani; Muhammad Riaz; Fasih Ullah Haider; Jingwen Liu; Muhammad Imran; Shafaqat Ali; Xiangdong Liu; Muhammad Qasim Shahid (Chemosphere, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Performance and emissions characteristics of tire pyrolysis oil in diesel engine: an experimental investigation - Haseeb Yaqoob; Hafiz Muhammad Ali; Haider Abbas; Osama Abid; Muhammad Ahmad Jamil; Talha Ahmed (Clean Technologies and Environmental Policy, 2023)

Unlocking the secrets of soil microbes: How decades-long contamination and heavy metals accumulation from sewage water and industrial effluents shape soil biological health - Idrees Haider; Muhammad Arif Ali; Muhammad Sanaullah; Niaz Ahmed; Sajjad Hussain; Muhammad Taimoor Shakeel; Syed Atif Hasan Naqvi; Javeed Shabbir Dar; Mahmoud Moustafa; Mohammed O. Alshaharni (Chemosphere, 2023)

Multiple phases of yttrium-doped molybdenum trioxide nanorods as efficient dye degrader and bactericidal agents with molecular docking analysis - Muhammad Ikram; Tahira Shujah; Anum Shahzadi; Ali Haider; Aqsa Rafique; Anwar Ul-Hamid; Walid Nabgan; Syed Karrar Haider; Thamraa Alshahrani; Mohammed M. Algaradah; S. Amber Yousaf; Junaid Haider (Chemosphere, 2023)

Assessment of rainwater harvesting potential for urban area under climate and land use changes using geo-informatics technology - Saif Haider; Muhammad Umer Masood; Muhammad Rashid; Tauqeer Ali; Chaitanya B. Pande; Fahad Alshehri; Ismail Elkhrachy (Urban Climate, 2023)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

Bio-ecology and the management of Chenopodium murale L.: A problematic weed in Asia - Ali Raza; Hafiz Haider Ali; Muhammad Saqlain Zaheer; Javaid Iqbal; Mahmoud Fathy Seleiman; Jaffar Sattar; Basharat Ali; Shumaila Khan; Tuba Arjumend; Bhagirath Singh Chauhan (Crop Protection, 2023)

Biochar alleviated the toxic effects of PVC microplastic in a soil-plant system by upregulating soil enzyme activities and microbial abundance - Attia Rubab Khalid; Tariq Shah; Muhammad Asad; Ahmad Ali; Eisha Samee; Fazal Adnan; Muhammad Faraz Bhatti; Sven Marhan; Claudia I. Kammann; Ghulam Haider (Environmental Pollution, 2023)

Exogenous Application of Moringa Leaf Extract Confers Salinity Tolerance in Sunflower by Concerted Regulation of Antioxidants and Secondary Metabolites - Fozia Farhat; Nadra Ashaq; Ali Noman; Muhammad Aqeel; Shameem Raja; Rashda Naheed; Muhammad Faisal Maqsood; Ijaz Haider; Arneeb Tariq (Journal of Soil Science and Plant Nutrition, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Lupeol, a plant triterpenoid mitigates salt induced stress: growth and antioxidative response of Brassica nigra under in vitro condition - Muhammad Zia; Joham Sarfraz Ali; Saad Hanif; Anila Sajjad; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Nickel (Ni) phytotoxicity and detoxification mechanisms: A review - Adnan Mustafa; Usman Zulfiqar; Muhammad Zahid Mumtaz; Maja Radziemska; Fasih Ullah Haider; Jiri Holatko; Tereza Hammershmiedt; Muhammad Naveed; Hassan Ali; Antonin Kintl; Qudsia Saeed; Jiri Kucerik; et al. (Chemosphere, 2023)

Evidence and Molecular Characterization of Multidrug Resistant Staphylococcus aureus Isolated From Equines in Pakistan - Farwa Anwaar; Muhammad Ijaz; Hamza Rasheed; Syed Faizan Ali Shah; Syed Ali Raza Haider; Muhammad Jawad Sabir (Journal of Equine Veterinary Science, 2023)

Co-opted directors and greenhouse gas emissions: Does ESG compensation matter? - Ammar Ali Gull; Aitzaz Ahsan Alias Sarang; Irfan Haider Shakri; Muhammad Atif (Journal of Cleaner Production, 2023)

Application of UAV photogrammetry and electrical resistivity tomography for characterization of a complex landslide: a case study from northwest Himalayas, Pakistan - Syed Ahatsham Haider; Matloob Hussain; Aamir Ali; Muhammad Faheem Abbasi; Saad Wani (Natural Hazards, 2023)

Polyvinylpyrrolidone and chitosan-coated magnetite (Fe3O4) nanoparticles for catalytic and antimicrobial activity with molecular docking analysis - Ayesha; Muhammad Imran; Ali Haider; Iram Shahzadi; Sawaira Moeen; Anwar Ul-Hamid; Walid Nabgan; Anum Shahzadi; Thamraa Alshahrani; Muhammad Ikram (Journal of Environmental Chemical Engineering, 2023)

Enhancement of biomethane production by huminite-enriched lignite pretreated with hydrogen peroxide - Weiting Zhang; Zaixing Huang; Dan Zhang; Gordana Medunić; Michael Urynowicz; Fang-Jing Liu; Hongguang Guo; Rizwan Haider; Muhammad Ishtiaq Ali; Asif Jamal; Huan He (International Journal of Coal Geology, 2023)

Microplastics alter soil enzyme activities and microbial community structure without negatively affecting plant growth in an agroecosystem - Tariq Shah; Ahmad Ali; Ghulam Haider; Muhammad Asad; Fazal Munsif (Chemosphere, 2023)

Different feedstocks of biochar affected the bioavailability and uptake of heavy metals by wheat (Triticum aestivum L.) plants grown in metal contaminated soil - Muhammad Ahmar Amin; Ghulam Haider; Muhammad Rizwan; H. Kate Schofield; Muhammad Farooq Qayyum; Muhammad Zia-ur-Rehman; Shafaqat Ali (Environmental Research, 2023)

Wavelet coherence of monsoon and large‐scale climate variabilities with precipitation in Pakistan - Azfar Hussain; Jianhua Cao; Shaukat Ali; Waheed Ullah; Sher Muhammad; Ishtiaq Hussain; Haider Abbas; Kalpana Hamal; Shankar Sharma; Mobeen Akhtar; Xiuqin Wu; Jinxing Zhou (International Journal of Climatology, 2022)
Monsoon and its teleconnection with earth system internal processes affect the spatiotemporal distribution of precipitation and water resources . In this paper, the wavelet coherence analysis has been utilized, a time and frequency domain methodology for comparing the spectral features of two independent time series superior to linear approaches. This technique is used to capture the significant modes of variabilities in the Indian Summer Monsoon Index (ISMI) and large‐scale climate indices (CIs) between ocean–atmosphere oscillations, like Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Southern Oscillation Index (SOI), North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO), and Arctic Oscillation (AO) over Pakistan. Precipitation time series during 1960–2016 revealed significant interannual coherences with ISMI, whereas the remaining CIs (IOD, ENSO, PDO, SOI, NAO, AMO, and AO) revealed interannual, decadal and interdecadal coherences. However, AO revealed strongest coherences in R‐II, III, and VI at interdecadal scales among all CIs. Overall, the interannual cycles on ISMI are 2.8 years, IOD 1–5.3 years, PDO 0–5.3 years, SOI 1–5.3 years, NAO 0–5 years, AO 0–5 years, and AMO 0–8.3 years. Whereas, the remaining CIs shared interdecadal coherences over particular regions. The ISMI displayed coherences (except in the UIB) with the large‐scale CIs over various homogenous regions on an interannual scale. The dominant influence of ISMI is observed in R‐II and III; the significant coherences in R‐II ranged from ~8 to 32 months (~0.8–2.8 years). The IOD and NAO have major coherences than the remaining large‐scale CIs ranging from ~16 to 64 months (1.3–5.3 years). The AO has the most significant coherences observed in R‐II, III, and VI on the decadal/interdecadal scale from 128 months and above (almost 10–15 years). On a 1.0‐year timescale, all homogenous regions demonstrated strong intermittent coherence with ISMI, IOD, ENSO, PDO, SOI, NAO, AMO, and AO. These findings have substantial implications for decision‐makers and scientists in Pakistan looking to enhance water resource planning and operations in the face of future climate uncertainties.

New trends in immunocastration and its potential to improve animal welfare: a mini review - Sohail Ahmed; Xunping Jiang; Guiqiong Liu; Amber Sadiq; Umar Farooq; Teketay Wassie; Ali Haider Saleem; Muhammad Zubair (Tropical Animal Health and Production, 2022)

Selection for resistance to pirimiphos-methyl, permethrin and spinosad in a field strain of Sitophilus oryzae: resistance risk assessment, cross-resistance potential and synergism of insecticides - Tiyyabah Khan; Hafiz Azhar Ali Khan; Muhammad Saleem Haider; Waheed Anwar; Adnan Akhter (Environmental Science and Pollution Research, 2022)

Probabilistic modeling and identifying fluctuations in annual extreme heatwave regimes of Karachi - Shahnillah Haider Rizvi; Muhammad Jawed Iqbal; Muhammad Ali (Meteorology and Atmospheric Physics, 2022)

Formulation and Evaluation of Topical Linezolid Nanoemulsion for Open Incision Wound in Diabetic Animal Model - Faheem Haider; Barkat Ali Khan; Muhammad Khalid Khan (AAPS PharmSciTech, 2022)

In silico analysis of a novel pathogenic variant c.7G > A in C14orf39 gene identified by WES in a Pakistani family with azoospermia - Haider Ali; Ahsanullah Unar; Muhammad Zubair; Sobia Dil; Farman Ullah; Ihsan Khan; Ansar Hussain; Qinghua Shi (Molecular Genetics and Genomics, 2022)

Inoculation of Azospirillum brasilense and exogenous application of trans-zeatin riboside alleviates arsenic induced physiological damages in wheat (Triticum aestivum) - Muhammad Saqlain Zaheer; Hafiz Haider Ali; Kehinde O. Erinle; Shabir Hussain Wani; Okon Godwin Okon; Muhammad Azhar Nadeem; Muhammad Nawaz; Muhammad Adnan Bodlah; Muhammad Mohsin Waqas; Javaid Iqbal; Ali Raza (Environmental Science and Pollution Research, 2022)

The effect of GnRH administration/insemination time on follicular growth rate, ovulation intervals, and conception rate of Nili Ravi buffalo heifers in 7 –day-CIDR Co-synch - Sajjad Haider; Ghazanfar Ali Chishti; Muhammad Usman Mehmood; Muhammad Ameen Jamal; Khalid Mehmood; Muhammad Shahzad; Muhammad Zahid Tahir (Tropical Animal Health and Production, 2021)

Seed Priming with Sodium Nitroprusside and H2O2 Confers Better Yield in Wheat Under Salinity: Water Relations, Antioxidative Defense Mechanism and Ion Homeostasis - Noman Habib; Qasim Ali; Shafaqat Ali; Muhammad Zulqarnain Haider; Muhammad Tariq Javed; Mubashra Khalid; Rashida Perveen; Abdulaziz Abdullah Alsahli; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2021)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

Trichlorfon resistance: its stability and impacts on biological parameters of Bactrocera zonata (Diptera: Tephritidae) - Muhammad Abubakar; Haider Ali; Sarfraz Ali Shad; Muhammad Anees; Muhammad Binyameen (Applied Entomology and Zoology, 2021)

Sewage wastewater reclamation with sand column filter and reduction of heavy metal accumulation in tomato and okra - Safina Naz; Muhammad Akbar Anjum; Shaghef Ejaz; Sajid Ali; Bushra Saddiq; Hasan Sardar; Sakeena Tul-Ain Haider (Environmental Science and Pollution Research, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Phyto-derivatives: an efficient eco-friendly way to manage Trogoderma granarium (Everts) (Coleoptera: Dermestidae) - Waqar Islam; Ali Noman; Komivi Senyo Akutse; Muhammad Qasim; Habib Ali; Ijaz Haider; Mohamed Hashem; Saad Alamri; Omar Mahmoud al Zoubi; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Empirical assessment of rockfall and debris flow risk along the Karakoram Highway, Pakistan - Sajid Ali; Rashid Haider; Wahid Abbas; Muhammad Basharat; Klaus Reicherter (Natural Hazards, 2021)
The Karakoram Highway links north Pakistan with southwest China. It passes through unique geomorphological, geological and tectonic setting. This study focused 200-km-long section of the highway starting from Besham until Chilas. Landslides are frequent and are mostly triggered by torrential rain during Monsoon and Westerlies, leading to highway blockade. Rockfall and debris flow are prime mode of slope failures. Regional to site-specific approach was implemented to assess risk associated with these two modes. Remote sensing-based techniques were used to identify potential hazardous sites, which were further investigated for risk assessment. Modified Pierson’s rockfall hazard rating system (RHRS) rated potential rockfalls, whereas semi-quantitative technique was employed to assess debris flows. Normalized scores of each site shaped the final map, further classified into four zones: very high, high, intermediate and low risk.

Characterization of fungal flora associated with sternorrhyncha insects of cotton plants - Waheed Anwar; Kiran Nawaz; Muhammad Asim Javed; Adnan Akhter; Ahmad Ali Shahid; Muhammad Saleem Haider; Muhammad Zia Ur Rehman; Sajid Ali (Biologia, 2021)

The effect of lead pollution on nutrient solution pH and concomitant changes in plant physiology of two contrasting Solanum melongena L. cultivars - Muhammad Tariq Javed; Noman Habib; Muhammad Sohail Akram; Qasim Ali; Muhammad Zulqurnain Haider; Kashif Tanwir; Asia Shauket; Hassan Javed Chaudhary (Environmental Science and Pollution Research, 2019)

Different nitrogen and biochar sources’ application in an alkaline calcareous soil improved the maize yield and soil nitrogen retention - Muhammad Farooq Qayyum; Mehak Ameer Abdullah; Muhammad Rizwan; Ghulam Haider; Muhammad Arif Ali; Muhammad Zafar-ul-Hye; Muhammad Abid (Arabian Journal of Geosciences, 2019)

Characteristics of pipe corrosion scales in untreated water distribution system and effect on water quality in Peshawar, Pakistan - Dilawar Farhan Shams; Saeed Islam; Baoyou Shi; Waliullah Khan; Buddhika Gunawardana; Maryam Saad; Muhammad Qasim; Haider Ali Javed; Sahib Gul Afridi; Muhammad Naeem; Gul Shahzada Khan (Environmental Science and Pollution Research, 2019)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Drought tolerance potential of Vigna mungo L. lines as deciphered by modulated growth, antioxidant defense, and nutrient acquisition patterns - Qasim Ali; Muhammad Zulqurnain Haider; Wasif Iftikhar; Sidra Jamil; M. Tariq Javed; Ali Noman; Muhammad Iqbal; Rashida Perveen (Brazilian Journal of Botany, 2016)

Prevalence of Waterborne Diseases in Exposed and Unexposed Clusters Using Biosand Filters in a Rural Community, Sindh, Pakistan - Munir Ahmed Sheikh; Muhammad Ayaz Mustufa; Taj Muhammad Laghari; Binafsha Manzoor; Syed Ali Haider; Safia Bibi; Firdous Imran Ali (Exposure and Health, 2016)

Foliar treatment with Lolium perenne (Poaceae) leaf extract alleviates salinity and nickel-induced growth inhibition in pea - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Muhammad Akbar Anjum; Hafiz Haider Ali; Neil Scott Mattson; Francisco Garcia-Sanchez (Brazilian Journal of Botany, 2016)

Genetics and mechanism of resistance to deltamethrin in the house fly, Musca domestica L., from Pakistan - Hafiz Azhar Ali Khan; Waseem Akram; Muhammad Saleem Haider (Ecotoxicology, 2015)

A distinct strain of chickpea chlorotic dwarf virus (genus Mastrevirus, family Geminiviridae) identified in cotton plants affected by leaf curl disease - Muhammad Tariq Manzoor; Muhammad Ilyas; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid; Rob W. Briddon (Archives of Virology, 2014)

Complete nucleotide sequences of two begomoviruses infecting Madagascar periwinkle (Catharanthus roseus) from Pakistan - Muhammad Ilyas; Kiran Nawaz; Muhammad Shafiq; Muhammad Saleem Haider; Ahmad Ali Shahid (Archives of Virology, 2013)

Shoot regeneration and free-radical scavenging activity in Silybum marianum L. - Bilal Haider Abbasi; Mubarak Ali Khan; Tariq Mahmood; Mushtaq Ahmad; Muhammad Fayyaz Chaudhary; Mir Ajab Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

The detection of antibody against peste des petits ruminants virus in Sheep, Goats, Cattle and Buffaloes - Haider Ali Khan; Muhammad Siddique; Sajjad-ur-Rahman; Muhammad Abubakar; Muhammad Ashraf (Tropical Animal Health and Production, 2008)

Prevalence and mortality rate of peste des petitis ruminant (ppr): possible association with abortion in goat - Muhammad Abubakar; Qurban Ali; Haider A. Khan (Tropical Animal Health and Production, 2008)